2022
DOI: 10.3399/bjgp.2022.0351
|View full text |Cite
|
Sign up to set email alerts
|

Changes in general practice use and costs with COVID-19 and telehealth initiatives: analysis of Australian whole-population linked data

Abstract: Background: In response to the COVID-19 pandemic, general practice in Australia underwent a rapid transition, including the rollout of population-wide telehealth, with uncertain impacts on general practitioner (GP) use and costs. Aim: To describe how use and costs of GP services changed in 2020—following the pandemic and introduction of telehealth—compared to 2019, and how this varied across population subgroups. Design and setting: Whole-of-population linked-data analysis, Australia. Method: Multi-Agency Data… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…A rapid review identified challenges with reduced digital access and digital literacy among the older adults and racial and ethnic minority groups, which are both groups at greater health risk from COVID-19 infections [12]. An Australian population study showed that the rapid uptake of telehealth during peak pandemic was not uniform, with the older adults, very young, and those with limited English language proficiency having a lower uptake of general practitioner (GP) telehealth services [13].…”
Section: Our Current Understanding Of the Digital Health Dividementioning
confidence: 99%
“…A rapid review identified challenges with reduced digital access and digital literacy among the older adults and racial and ethnic minority groups, which are both groups at greater health risk from COVID-19 infections [12]. An Australian population study showed that the rapid uptake of telehealth during peak pandemic was not uniform, with the older adults, very young, and those with limited English language proficiency having a lower uptake of general practitioner (GP) telehealth services [13].…”
Section: Our Current Understanding Of the Digital Health Dividementioning
confidence: 99%